Ag+‐Gated Surface Chemistry of Gold Nanoparticles and Colorimetric Detection of Acetylcholinesterase. Issue 31 (3rd July 2018) - Zhang, Jiangjiang; Zheng, Wenshu; Jiang, Xingyu
Abstract: Chemical regulation of enzyme‐mimic activity of nanomaterials is challenging because it requires a precise understanding of the surface chemistry and mechanism, and rationally designed applications. Herein, Ag + ‐gated peroxidase activity is demonstrated by successfully modulating surface chemistry of cetyltrimethylammonium bromide‐capped gold nanoparticles (CTAB‐AuNPs). A surface blocking effect of long‐chain molecules on surfaces of AuNPs that inhibit peroxidase activity of AuNPs is found. Ag + ions can selectively bind on the surfaces of AuNPs and competitively destroy CTAB membrane forming Ag + @CTAB‐AuNPs complexes to result in enhanced peroxidase activity. Ag + @CTAB‐AuNPs show the highest peroxidase activity compared to similar‐sized citrate‐capped and ascorbic acid‐capped AuNPs. Ag + @CTAB‐AuNPs can potentially develop into analyte‐responsive systems and exhibit advantages in the optical sensing field. For example, the Ag + @CTAB‐AuNPs system shows an enhanced sensitivity and selectivity for acetylcholinesterase activity sensing compared to other methods. Abstract : Knock, knock! Ag + ‐gated surface chemistry of cetyltrimethylammonium bromide‐gold nanoparticles (CTAB‐AuNPs) opens a door to better understanding the chemical regulation of enzymatic activity of nanomaterial. A simple but efficient, analyte‐responsive system of Ag + @CTAB‐AuNPs enables the sensitive and selective detection of acetylcholinesterase activity.